INTERNALISASI NILAI-NILAI SOSIO-KULTURAL BERBASIS ETNO-RELIGI DI MAN YOGYAKARTA III - Rohman, Miftahur; Mukhibat, Mukhibat (Program Studi Pendidikan Agama Islam, 2017)
INTERNALIZATION OF SOCIO-CULTURAL VALUE BASED ON ETHNO-RELIGIOUS IN MAN YOGYAKARTA III. The phenomenon of violence in the name of religion, ethnicity, and culture has shown that humans have failed to understand heterogeneity, diversity, and plurality as main characteristics of the Islamic educational institutions, such as Madrasa. For responding that phenomenon, MAN Yogyakarta III (Mayoga) believes that they will create the humanist and inclusive education. This research with phenomenological approach and qualitative descriptive method was focused on best practice done by Mayoga, humanist and inclusive education. The results showed that the values of diversity in Mayoga were internalized in learning activities by integrating the values of religion, culture, and diversity. The integration generates socio-cultural values, such as appreciating ‘mazhab’ differences in religious practices, cultural assimilation and regional languages, tolerance and human rights, and social coherence among the school communities. Thus, the social values that grow in Mayoga can keep the values of social cohesion among people in Madrasa.